Effect of Music Therapy on Intensity of Labor Pain among Primigravid Mothers admitted in a Tertiary Level Hospital - Gautam, Samjhana; Dhakal Chalise, Gita; Bharati, Mamata; Shrestha, Sarala (Journal of Nepal Health Research Council, 2023)
Background: Childbirth is a most welcomed and positive life experience for the majority of women, despite the pain. Most of them manage it well with minimal assistance while few of them require some intervention to reduce the pain. The objective of this study was to find out the effect of music therapy on intensity of labor pain among primigravid women. Methods: A quasi-experimental pre-test post-test non-equivalent control group design was used. Sample consisted of 42 primigravid women admitted in labor room of a teaching hospital in Kathmandu. The intensity of labor pain was measured using Visual Analogue Scale and Behavior Rating Scale in latent and active phase of labor in both experimental and control groups. Then 30 minutes of music therapy was provided to the experimental group in the latent and active phase of labor. The post-test was carried out in both groups after the music therapy to experimental group during the latent and active phase using the same instruments. The collected data was entered in Statistical Package for Social Sciences version 16. Descriptive statistics and inferential statistics were used to describe the findings. Findings: The mean difference of total pain between experimental and control groups during latent phase was 1.9 (t=2.31, p=0.023) in pre-test and 6.57 (t=3.91, p=0.000) in post-test. The mean difference of total pain between experimental and control groups during active phase was 1.00 (t=1.08, p=0.286) during pre-test and 6.95(t=3.744, p=0.001) during post-test. Conclusions: Music therapy tends to reduce labor pain both during the latent and active phase of labor.